Do not shoot the messenger: ICES advice for an ecosystem approach to fisheries management in the European Union. (4th October 2017) - Ballesteros, Marta; Chapela, Rosa; Ramírez-Monsalve, Paulina; Raakjaer, Jesper; Hegland, Troels J; Nielsen, Kåre N; Laksá, Unn; Degnbol, Poul
Abstract: The International Council for the Exploration of the Sea (ICES) occupies a central role in the advice system to support the implementation of an ecosystem approach to fisheries management (EAFM) in the European Union (EU). Despite improvements, its capacity to deliver ecosystem advice seems to be far from a fully functional operational framework. To what extent availability of appropriate scientific advice is a barrier for a more widespread use of an EAFM in Europe remains an open question. Building on the findings of a large research project, this article explores what advice ICES can provide. The article concludes that: (i) ICES has taken a leading role in generating an EAFM framework in which management decisions can operate; (ii) the advice "suppliers" and the advice "users" agree on the feasibility of using existing knowledge to "do EAFM now"; (iii) ICES can address a range of shortcomings, but some of the present bottlenecks demand concerted action between the advisory system and the political realm. The implementation of an EAFM requires consistency between science and management. ICES appears as well-suited to facilitate the dialogue on applying an EAFM in the EU, but it is unrealistic to expect ICES to produce all the answers.